An anti-relaxation coating for alkali metal atom cells and a method of making the same
Patent Information
- Application Number
- CN202610695069.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-20
- Publication Date
- 2026-09-04
AI Technical Summary
但是,原子会与惰性缓冲气体发生碰撞,导致精细能级中心频率的偏移,使得原子共振峰展宽,干扰原子自旋的一致性,降低了接收信号的灵敏度
本申请针对现有关于降低碱金属原子退极化率,提升碱金属原子气室寿命方法中普遍存在改善效果不明显的难题,采用热法原子层沉积技术,在碱金属原子气室内壁镀制十八烷基三聚硅烷/全氟辛基三聚硅氧烷复合涂层。复合涂层中,十八烷基三聚硅烷(ODS-3)层抑制碱金属原子与气室内壁的非弹性碰撞,全氟辛基三聚硅氧烷(PF-TH)层用于提升抗驰豫涂层的高温性能和疏水性能,从而降低碱金属原子退极化率,延长碱金属原子气室寿命,实现相干布局囚禁(CPT)磁力仪灵敏度的提升。本申请采用热法原子层沉积技术,可以有效控制涂层组分,极大提升涂层致密度,最大程度消除涂层中水分子的影响,从而有效延长碱金属原子气室的寿命。
Smart Images

Figure CN122687166A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of vacuum coating technology, and more specifically, to an anti-relaxation composite coating for an alkali metal atom gas chamber and its preparation method. Background Technology
[0002] The coherent layout trapping (CPT) atomic magnetometer is a high-sensitivity magnetic field measurement device based on quantum optics principles. It has advantages such as miniaturization and stable performance under dynamic environments, and has broad application prospects in deep space exploration, UAV aeromagnetics, astronomical research and other fields.
[0003] The alkali metal atom gas cell is a key factor affecting the sensitivity of the CPT atomic magnetometer. The polarized atoms inside are prone to collisions with other atoms or the cell walls, and are also affected by external magnetic fields, temperature fields and other field effects, which cause the polarized atoms to depolarize and the quantum state of the atomic ensemble to return to equilibrium.
[0004] To extend the lifespan of alkali metal atom chambers, two common techniques are employed: filling them with an inert buffer gas or coating their inner walls with an anti-relaxation coating. Filling with an inert buffer gas prevents collisions between polarized atoms and the chamber walls, shortens the mean free path of atoms, and prolongs the interaction time between atoms and light, thereby reducing the depolarization rate of atoms. However, collisions between atoms and the inert buffer gas cause a shift in the center frequency of the fine energy levels, broadening the atomic resonance peaks, interfering with the uniformity of atomic spin, and reducing the sensitivity of the received signal. Coating the inner walls of the alkali metal atom chamber with an anti-relaxation coating forms a protective barrier. This coating not only has minimal impact on the motion and spin state of polarized atoms but also significantly reduces direct collisions between atoms and the chamber walls, effectively improving atomic utilization and pump light utilization. Therefore, coating the inner walls of the alkali metal atom chamber with an anti-relaxation coating is an important way to improve the sensitivity of CPT magnetometers.
[0005] Therefore, the research on the anti-relaxation coating system materials and corresponding preparation methods of the inner wall of the alkali metal atomic gas chamber is of great significance. The relevant results can provide technical support for the research and development and application of CPT magnetometers under more severe environments. Summary of the Invention
[0006] To achieve the above objectives, this application provides an anti-relaxation composite coating for an alkali metal atom chamber and its preparation method. An octadecyltrisilane / perfluorooctyltrisiloxane composite coating is deposited on the inner wall of the alkali metal atom chamber using thermal atomic layer deposition technology to reduce the depolarization rate of the alkali metal atoms, extend the lifetime of the alkali metal atom chamber, and thereby improve the sensitivity of the coherent layout trapping (CPT) magnetometer.
[0007] This invention provides the following technical solution: In a first aspect, the present invention provides an anti-relaxation composite coating for an alkali metal atom gas cell, comprising: an anti-relaxation layer and a modified layer, wherein: the anti-relaxation layer comprises octadecyltrisilane (ODS-3) deposited on the inner wall of the alkali metal atom gas cell; and the modified layer comprises perfluorooctyltrisiloxane (PF-TH) deposited on the surface of the anti-relaxation layer.
[0008] Furthermore, the thickness of the anti-relaxation composite coating is 40~60 nm.
[0009] Furthermore, the thickness of the anti-relaxation layer is 30~50 nm, and the thickness of the modified layer is 10 nm.
[0010] Furthermore, the inner wall material of the alkali metal atom gas chamber is borosilicate glass.
[0011] Furthermore, the raw materials of the anti-relaxation layer, on a molar basis, include: 1 part of the anti-relaxation layer precursor and 3 parts of the hydroxyl source; the raw materials of the modified layer, on a molar basis, include: 1 part of the modified layer precursor and 3 parts of the hydroxyl source.
[0012] Furthermore, the anti-relaxation layer precursor is octadecyltrichlorosilane (OTS).
[0013] Furthermore, the modified layer precursor is perfluorooctyltrichlorosilane (PFOTS).
[0014] Furthermore, the hydroxyl source is water or O3, preferably deionized water.
[0015] Secondly, the present invention provides a method for preparing an anti-relaxation composite coating, comprising the following steps: Step 0: Place the alkali metal atom gas chamber in the reaction chamber of the atomic layer deposition equipment, evacuate the vacuum, and heat the chamber. Step 1: Prepare the anti-relaxation layer using thermal atomic layer deposition (TLD) technology; Step 2: Re-evacuate the reaction chamber and heat it up. Step 3: Prepare the modified layer using thermal atomic layer deposition technology.
[0016] Furthermore, in step 0, the vacuum is evacuated to 1×10⁻⁶. -2 ~1×10 -3 Pa, heated to 150~250℃.
[0017] Further, in step 1, the preparation of the anti-relaxation layer using thermal atomic layer deposition technology includes: Step 10: Heat the source bottle storing the anti-relaxation layer precursor; Step 11: The anti-relaxation layer precursor is transported through the reaction chamber in the form of a gas pulse via nitrogen gas to form a monoadsorption layer by chemical adsorption. Step 12: Introduce nitrogen gas into the reaction chamber to fully remove any unadsorbed anti-relaxation layer precursor; Step 13: Introduce a hydroxyl source into the reaction chamber to allow it to react with the adsorbed anti-relaxation layer precursor on the surface. Step 14: Introduce nitrogen gas into the reaction chamber to remove excess reaction gases and reaction byproducts, forming an anti-relaxation layer.
[0018] Furthermore, in step 10, the temperature is raised to 50~90℃.
[0019] Furthermore, in step 11, the flow rate of the anti-relaxation layer precursor is 120~200 sccm, the introduction time is 1.0~3.0 s, and the nitrogen flow rate is 150~250 sccm.
[0020] Furthermore, in step 12, the nitrogen flow rate is 150~250 sccm, and the introduction time is 10~20 s.
[0021] Furthermore, in step 13, the flow rate of the hydroxyl source is 150~250 sccm, and the inlet time is 5~10 s.
[0022] Furthermore, in step 14, the nitrogen flow rate is 150~250 sccm, and the introduction time is 10~20 s.
[0023] Furthermore, in step 2, a vacuum is drawn to 1×10⁻⁶. -2 ~1×10 -3 Pa, heat to 80~150℃.
[0024] Further, in step 3, the preparation of the modified layer using thermal atomic layer deposition technology includes the following steps: Step 30: Heat the source bottle storing the modified layer precursor; Step 31: The modified layer reaction precursor is transported through the reaction chamber in the form of a gas pulse via nitrogen gas to form a monoadsorption layer by chemical adsorption. Step 32: Introduce nitrogen gas into the reaction chamber to fully remove any unadsorbed modified layer reaction precursors; Step 33: Introduce a hydroxyl source into the reaction chamber to allow it to react with the adsorbed modified layer precursor on the surface. Step 34: Introduce nitrogen gas into the reaction chamber to remove excess reaction gases and reaction byproducts, forming a modified layer.
[0025] Furthermore, in step 30, the temperature is raised to 50~80℃.
[0026] Further, in step 31, the flow rate of the modified layer reaction precursor is 120~200 sccm, the introduction time is 1.0~5.0 s, and the nitrogen flow rate is 150~250 sccm.
[0027] Furthermore, in step 32, the nitrogen flow rate is 150~250 sccm, and the introduction time is 10~20 s.
[0028] Furthermore, in step 33, the flow rate of the hydroxyl source is 150~250 sccm, and the introduction time is 5~10 s.
[0029] Furthermore, in step 34, the nitrogen flow rate is 150~250 sccm, and the introduction time is 10~20 s.
[0030] Furthermore, one deposition cycle is performed to prepare the anti-relaxation coating using the thermal atomic layer deposition technique, resulting in a single anti-relaxation layer with a thickness equal to that of a single molecule. The deposition cycle is repeated N times until the desired thickness of the anti-relaxation layer is obtained.
[0031] Furthermore, one deposition cycle is performed to prepare the modified layer using the thermal atomic layer deposition technique, resulting in a single modified layer with a thickness equal to that of a single molecule. The deposition cycle is repeated N times until the modified layer of the desired thickness is obtained.
[0032] Furthermore, the thickness of the individual molecule is 0.10~0.30 nm.
[0033] Furthermore, the Nth time is 50 to 100 times.
[0034] The technical solution of this application has the following beneficial effects: This application addresses the common problem of limited improvement in existing methods for reducing the depolarization rate of alkali metal atoms and extending the lifespan of alkali metal atom chambers. It employs thermal atomic layer deposition (TBLD) to deposit an octadecyltrisilane / perfluorooctyltrisiloxane composite coating on the inner wall of the alkali metal atom chamber. In the composite coating, the octadecyltrisilane (ODS-3) layer suppresses inelastic collisions between alkali metal atoms and the inner wall, while the perfluorooctyltrisiloxane (PF-TH) layer enhances the high-temperature performance and hydrophobicity of the anti-relaxation coating. This reduces the depolarization rate of alkali metal atoms, extends the lifespan of the alkali metal atom chamber, and improves the sensitivity of the coherent layout trapping (CPT) magnetometer. The use of thermal atomic layer deposition in this application allows for effective control of the coating composition, significantly increases coating density, and minimizes the influence of water molecules in the coating, thereby effectively extending the lifespan of the alkali metal atom chamber. Attached Figure Description
[0035] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0036] Figure 1 This is a schematic diagram of the anti-relaxation composite coating for the alkali metal atom gas chamber provided in the embodiments of this application. In the picture: 1- High borosilicate glass substrate (inner wall of alkali metal atom gas chamber); 2-Anti-relaxation layer; 3-Modified layer. Detailed Implementation
[0037] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0038] Where specific experimental steps or conditions are not specified in the embodiments, they can be performed according to the conventional experimental steps or conditions described in the literature in this field. All raw materials or instruments used are commercially available conventional products, including but not limited to those used in the embodiments of this application.
[0039] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The following will be discussed in conjunction with the appendix. Figure 1This application provides a detailed description of an anti-relaxation composite coating for an alkali metal atom gas cell and its preparation method.
[0040] The technical problem this invention aims to solve is the common difficulty in achieving significant improvements in existing methods for reducing the depolarization rate of alkali metal atoms and extending the lifespan of alkali metal atom gas chambers. This invention proposes a method for depositing an anti-relaxation coating system on the inner wall of an alkali metal atom gas chamber and its preparation. The basic principle is to prepare an octadecyltrisilane / perfluorooctyltrisiloxane composite coating on the surface of the inner wall of the alkali metal atom gas chamber. The octadecyltrisilane (ODS-3) layer acts as an anti-relaxation layer, suppressing inelastic collisions between alkali metal atoms and the inner wall of the gas chamber. The perfluorooctyltrisiloxane (PF-TH) layer acts as a modifying coating, enhancing the high-temperature performance and hydrophobic properties of the anti-relaxation layer. This application employs thermal atomic layer deposition (TLD) technology, which effectively controls the coating composition, significantly improves the density of the anti-relaxation layer, and minimizes the influence of water molecules in the coating, thereby effectively extending the lifespan of the alkali metal atom gas chamber.
[0041] Please see Figure 1 The anti-relaxation composite coating for alkali metal atom gas chamber provided in this application embodiment is used to improve the lifespan of alkali metal atom gas chamber. It includes an anti-relaxation layer 2 and a modification layer 3. The anti-relaxation layer 2 is deposited on the inner wall of the alkali metal atom gas chamber (the material is a high borosilicate glass substrate 1), and the modification layer 3 is deposited on the surface of the anti-relaxation layer 2.
[0042] The thickness of the anti-relaxation composite coating of the alkali metal atom gas cell is 40~60 nm, of which the thickness of the anti-relaxation layer 2 is 30~50 nm and the thickness of the modified layer 3 is 10 nm.
[0043] A thermal atomic layer deposition (TAD) technique was used to deposit an anti-relaxation layer 2 on the surface of a borosilicate glass substrate 1. Then, a modification layer 3 was deposited on the surface of the anti-relaxation layer 2 using the same technique. The raw materials for the anti-relaxation layer 2 included an anti-relaxation layer precursor and a hydroxyl source, and the raw materials for the modification layer 3 included a modification layer precursor and a hydroxyl source.
[0044] Specifically, in a preferred embodiment of this application, the anti-relaxation layer precursor is octadecyltrichlorosilane (OTS), the modified layer precursor is perfluorooctyltrichlorosilane (PFOTS), and the hydroxyl source is deionized water.
[0045] The method for preparing the anti-relaxation composite coating of the metal atom gas chamber provided in this application includes the following steps: Step 0: Place the alkali metal atom gas chamber in the reaction chamber of the atomic layer deposition equipment, evacuate the vacuum, and heat the chamber. Step 1: Prepare the anti-relaxation layer 2 using thermal atomic layer deposition technology; Step 2: Re-evacuate the reaction chamber and heat it up; Step 3: Prepare modified layer 3 using thermal atomic layer deposition technology.
[0046] One deposition cycle is performed to prepare the anti-relaxation layer 2 using a single thermal atomic layer deposition technique. A single anti-relaxation layer 2 is obtained, and the thickness of a single anti-relaxation layer 2 is the thickness of a single molecule. The deposition cycle is repeated N times until the desired thickness of the anti-relaxation layer 2 is obtained.
[0047] One deposition cycle is performed to prepare the modified layer 3 using thermal atomic layer deposition technology. A single modified layer 3 is obtained, and the thickness of a single modified layer 3 is the thickness of a single molecule. The deposition cycle is repeated N times until the modified layer 3 of the required thickness is obtained.
[0048] The method for preparing the anti-relaxation composite coating of the metal atom gas chamber provided in this application includes the following steps: Step 0: Place the alkali metal atom gas chamber in the reaction chamber of the atomic layer deposition equipment, evacuate the vacuum, and heat the chamber. Step 1: Prepare the anti-relaxation layer 2 using thermal atomic layer deposition technology; Step 2: Re-evacuate the reaction chamber and heat it up; Step 3: Prepare modified layer 3 using thermal atomic layer deposition technology.
[0049] One deposition cycle is performed to prepare the anti-relaxation layer 2 using a single thermal atomic layer deposition technique. A single anti-relaxation layer 2 is obtained, and the thickness of a single anti-relaxation layer 2 is the thickness of a single molecule. The deposition cycle is repeated N times until the desired thickness of the anti-relaxation layer 2 is obtained.
[0050] One deposition cycle is performed to prepare the modified layer 3 using thermal atomic layer deposition technology. A single modified layer 3 is obtained, and the thickness of a single modified layer 3 is the thickness of a single molecule. The deposition cycle is repeated N times until the modified layer 3 of the required thickness is obtained.
[0051] Specifically, in the embodiments of this application, in step 0, the alkali metal atom gas chamber is placed in the reaction chamber of the atomic layer deposition equipment, and the vacuum is evacuated to 1×10⁻⁶. -2 ~1×10 -3 Pa, heated to 150~250 ℃.
[0052] In step 1, an anti-relaxation layer 2 is prepared using thermal atomic layer deposition technology, including: Step 10: Heat the source bottle storing the anti-relaxation layer precursor to 50~90 ℃ to make the anti-relaxation layer precursor gaseous; Step 11: The anti-relaxation layer precursor is passed through the reaction chamber in the form of a gas pulse via nitrogen transport to form a monoadsorption layer by chemical adsorption. The flow rate of the anti-relaxation layer precursor is 120~200 sccm, the passage time is 1.0~3.0 s, and the nitrogen flow rate is 150~250 sccm. Step 12: Introduce nitrogen into the reaction chamber to fully remove unadsorbed anti-relaxation layer precursors. The nitrogen flow rate is 150~250 sccm and the introduce time is 10~20 s. Step 13: Introduce a hydroxyl source into the reaction chamber to react with the adsorbed anti-relaxation layer precursor on the surface. The flow rate of the hydroxyl source is 150-250 sccm and the introduction time is 5-10 s. Step 14: Introduce nitrogen gas into the reaction chamber at a flow rate of 150-250 sccm for 10-20 s to remove excess reaction gases and reaction byproducts, forming the anti-relaxation layer 2.
[0053] In step 2, the reaction chamber is re-evacuated to 1×10⁻⁶ ℃. -2 ~1×10 -3 Pa, heated to 80~150 ℃.
[0054] In step 3, modified layer 3 is prepared using thermal atomic layer deposition technology, including: Step 30: Heat the source bottle containing the modified layer precursor to 50~80℃; Step 31: The modified layer reaction precursor is passed through the reaction chamber in the form of a gas pulse via nitrogen transport to form a single adsorption layer by chemical adsorption. The flow rate of the modified layer reaction precursor is 120~200 sccm, the passage time is 1.0~5.0 s, and the nitrogen flow rate is 150~250 sccm. Step 32: Introduce nitrogen gas into the reaction chamber to fully remove the unadsorbed modified layer reaction precursor. The nitrogen flow rate is 150~250 sccm and the introduce time is 10~20 s. Step 33: Introduce a hydroxyl source into the reaction chamber to react with the adsorbed modified layer reaction precursor on the surface. The flow rate of the hydroxyl source is 150-250 sccm and the introduction time is 5-10 s. Step 34: Introduce nitrogen gas into the reaction chamber at a flow rate of 150-250 sccm for 10-20 s to remove excess reaction gases and reaction byproducts, forming modified layer 3.
[0055] One deposition cycle consists of preparing the anti-relaxation layer 2 or modified layer 3 using thermal atomic layer deposition (ALD). A single anti-relaxation layer 2 or modified layer 3 is obtained, with a thickness equal to that of a single molecule. This deposition cycle is repeated N times until the desired thickness of the anti-relaxation layer 2 or modified layer 3 is obtained. The thickness of a single molecule is 0.10–0.30 nm, and N cycles are 50–100.
[0056] Specifically, in a preferred embodiment of this application, the method for preparing the anti-relaxation composite coating of the metal atom gas chamber provided in this application includes the following steps: Step 0: Place the alkali metal atom gas chamber into the reaction chamber of the atomic layer deposition equipment and evacuate to 1×10⁻⁶. -3 Pa, heated to 200 ℃.
[0057] Step 1: Prepare the anti-relaxation layer 2 using thermal atomic layer deposition technology, including: Step 10: Heat the source bottle storing octadecyltrichlorosilane (OTS) to 80 °C to make OTS gaseous; Step 11: OTS is passed through the reaction chamber in the form of gas pulses via nitrogen transport to form a monoadsorption layer by chemical adsorption. The OTS flow rate is 160 sccm, the introduction time is 2.0 s, and the nitrogen flow rate is 200 sccm. Step 12: Introduce nitrogen into the reaction chamber to fully remove unadsorbed OTS. The nitrogen flow rate is 200 sccm and the introduce nitrogen for 15 s. Step 13: Deionized water is introduced into the reaction chamber to react with the adsorbed OTS on the surface. The flow rate of the deionized water is 200 sccm and the introduction time is 8 s. Step 14: Nitrogen gas is introduced into the reaction chamber at a flow rate of 200 sccm for 15 s to remove excess reaction gases and byproducts, forming an octadecyltrisilane (ODS-3) anti-relaxation layer 2. The thickness of the ODS-3 anti-relaxation layer 2 is 0.3 nm.
[0058] Repeat step 1 until the thickness of the ODS-3 anti-relaxation layer 2 reaches 30 nm.
[0059] Step 2: Re-evacuate the reaction chamber to a vacuum level of 1×10⁻⁶. -3 Pa, heated to 120℃.
[0060] Step 3, preparing modified layer 3 using thermal atomic layer deposition technology, including: Step 30: Heat the source bottle storing perfluorooctyltrichlorosilane (PFOTS) to 80°C; Step 31: PFOTS is passed through the reaction chamber in the form of gas pulses via nitrogen transport to form a monoadsorption layer by chemical adsorption. The PFOTS flow rate is 160 sccm, the introduction time is 3.0 s, and the nitrogen flow rate is 200 sccm. Step 32: Introduce nitrogen gas into the reaction chamber to fully remove unadsorbed PFOTS. The nitrogen flow rate is 200 sccm and the introduce nitrogen gas for 15 s. Step 33: Deionized water is introduced into the reaction chamber to react with the adsorbed PFOTS on the surface. The flow rate of PFOTS is 200 sccm and the introduction time is 8 s. Step 34: Nitrogen gas is introduced into the reaction chamber at a flow rate of 200 sccm for 15 s to remove excess reaction gases and byproducts, forming perfluorooctyltripolysiloxane (PF-TH) modified layer 3. The thickness of PF-TH modified layer 3 is 0.1 nm.
[0061] Repeat step 3 until the thickness of the PF-TH modified layer 3 reaches 10 nm.
[0062] The ODS-3 / PF-TH composite coating prepared in this preferred embodiment is deposited on the inner wall of the alkali metal atom gas cell (high borosilicate glass substrate 1) with a thickness of 40 nm. Among them, the ODS-3 anti-relaxation layer 2 has a thickness of 30 nm and the PF-TH modified coating 3 has a thickness of 10 nm.
[0063] This application addresses the common problem of limited improvement in existing methods for reducing the depolarization rate of alkali metal atoms and extending the lifespan of alkali metal atom chambers. It employs thermal atomic layer deposition (TBLD) technology to deposit an octadecyltrisilane / perfluorooctyltrisiloxane composite coating on the inner wall of the alkali metal atom chamber. In the composite coating, the octadecyltrisilane (ODS-3) layer suppresses inelastic collisions between alkali metal atoms and the inner wall, while the perfluorooctyltrisiloxane (PF-TH) layer enhances the high-temperature performance and hydrophobic properties of the anti-relaxation coating. This reduces the depolarization rate of alkali metal atoms, extends the lifespan of the alkali metal atom chamber, and improves the sensitivity of the coherent layout trapping (CPT) magnetometer.
[0064] This application employs thermal atomic layer deposition technology, which can effectively control the coating composition, greatly improve the coating density, and minimize the influence of water molecules in the coating, thereby effectively extending the life of the alkali metal atom gas chamber.
[0065] Obviously, the above embodiments are merely illustrative examples and not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A composite coating for resisting relaxation of alkali metal atom gas cells, characterized in that, include: The anti-relaxation layer and the modified layer, wherein: the anti-relaxation layer comprises octadecyltrisilane (ODS-3), which is deposited on the inner wall of the alkali metal atom gas cell; the modified layer comprises perfluorooctyltrisiloxane (PF-TH), which is deposited on the surface of the anti-relaxation layer.
2. The anti-relaxation composite coating according to claim 1, characterized in that, The inner wall material of the alkali metal atom gas chamber is high borosilicate glass; the thickness of the anti-relaxation composite coating is 40~60 nm, wherein the thickness of the anti-relaxation layer is 30~50 nm, and the thickness of the modified layer is 10 nm.
3. The anti-relaxation composite coating according to claim 1, characterized in that, The raw materials for the anti-relaxation layer, on a molar basis, include: 1 part of the anti-relaxation layer precursor and 3 parts of the hydroxyl source; the raw materials for the modified layer, on a molar basis, include: 1 part of the modified layer precursor and 3 parts of the hydroxyl source, wherein the anti-relaxation layer precursor is octadecyltrichlorosilane (OTS), the modified layer precursor is perfluorooctyltrichlorosilane (PFOTS), and the hydroxyl source is water or O3, preferably deionized water.
4. The method for preparing the anti-relaxation composite coating according to any one of claims 1 to 3, characterized in that, Includes the following steps: Step 0: Place the alkali metal atom gas chamber in the reaction chamber of the atomic layer deposition equipment, evacuate the vacuum, and heat the chamber. Step 1: Prepare an anti-relaxation layer using thermal atomic layer deposition (TLD) technology; Step 2: Re-evacuate the reaction chamber and heat it up; Step 3: Prepare the modified layer using thermal atomic layer deposition technology.
5. The preparation method according to claim 4, characterized in that, In step 0, a vacuum is drawn to 1×10⁻⁶. -2 ~1×10 -3 Pa, heat to 150~250℃; in step 2, evacuate to 1×10 -2 ~1×10 -3 Pa, heat to 80~150℃.
6. The preparation method according to claim 4, characterized in that, The preparation of the anti-relaxation layer using thermal atomic layer deposition technology includes the following steps: Step 10: Heat the source bottle storing the anti-relaxation layer precursor; Step 11: The anti-relaxation layer precursor is transported through the reaction chamber in the form of a gas pulse via nitrogen gas to form a monoadsorption layer by chemical adsorption. Step 12: Introduce nitrogen gas into the reaction chamber to fully remove any unadsorbed anti-relaxation layer precursor; Step 13: Introduce a hydroxyl source into the reaction chamber to allow it to react with the adsorbed anti-relaxation layer precursor on the surface. Step 14: Introduce nitrogen gas into the reaction chamber to remove excess reaction gases and reaction byproducts, forming an anti-relaxation layer.
7. The preparation method according to claim 6, characterized in that, In step 10, the temperature is raised to 50~90℃; in step 11, the flow rate of the anti-relaxation layer precursor is 120~200 sccm, the introduction time is 1.0~3.0 s, and the nitrogen flow rate is 150~250 sccm; in step 12, the nitrogen flow rate is 150~250 sccm, and the introduction time is 10~20 s; in step 13, the flow rate of the hydroxyl source is 150~250 sccm, and the introduction time is 5~10 s; in step 14, the nitrogen flow rate is 150~250 sccm, and the introduction time is 10~20 s.
8. The preparation method according to claim 4, characterized in that, The preparation of the modified layer using thermal atomic layer deposition technology includes the following steps: Step 30: Heat the source bottle storing the modified layer precursor; Step 31: The modified layer reaction precursor is transported through the reaction chamber in the form of a gas pulse via nitrogen gas to form a monoadsorption layer by chemical adsorption. Step 32: Introduce nitrogen gas into the reaction chamber to fully remove any unadsorbed modified layer reaction precursors; Step 33: Introduce a hydroxyl source into the reaction chamber to allow it to react with the adsorbed modified layer precursor on the surface. Step 34: Introduce nitrogen gas into the reaction chamber to remove excess reaction gases and reaction byproducts, forming a modified layer.
9. The preparation method according to claim 8, characterized in that, In step 30, the temperature is raised to 50~80℃; in step 31, the flow rate of the modified layer reaction precursor is 120~200 sccm, the introduction time is 1.0~5.0 s, and the nitrogen flow rate is 150~250 sccm; in step 32, the nitrogen flow rate is 150~250 sccm, and the introduction time is 10~20 s; in step 33, the flow rate of the hydroxyl source is 150~250 sccm, and the introduction time is 5~10 s; in step 34, the nitrogen flow rate is 150~250 sccm, and the introduction time is 10~20 s.
10. The preparation method according to claim 4, characterized in that, One deposition cycle is performed to prepare the anti-relaxation coating using the thermal atomic layer deposition technique, resulting in a single anti-relaxation layer with a thickness equal to that of a single molecule. This deposition cycle is repeated N times until the desired thickness of the anti-relaxation layer is obtained. Similarly, one deposition cycle is performed to prepare the modified layer using the thermal atomic layer deposition technique, resulting in a single modified layer with a thickness equal to that of a single molecule. This deposition cycle is repeated N times until the desired thickness of the modified layer is obtained.
11. The preparation method according to claim 10, characterized in that, The thickness of a single molecule is 0.10~0.30 nm, and the N times is 50~100 times.